Upaya Meningkatkan Pengetahuan Tentang Kesehatan Reproduksi dan Anemia Melalui Metode BELANJA (Blended Learning Kesehatan Reproduksi Remaja) - Choiriyah, Muladefi; Merdikawati, Ayut; Kartika, Annisa Wuri; Kristianingrum, Niko Dima (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
The Covid-19 pandemic has made adolescents access the internet for education and other information, including harmful content. Public Vocational High School 2 Malang is one of the largest schools, totaling 1869 students. In this school, educational health is given once at the beginning of the orientation period and still does not cover adolescent reproductive health. Therefore, there is a need for assistance through blended learning methods to improve adolescent reproductive health. This activity aims to increase students' knowledge about sexual reproductive health. The targets were 92 Public Vocational High School 2 Malang students, a nursing assistant program, and tenth-grade students. An education session was conducted in September 2022 for 3 weeks with blended learning. The SHARING AJA (Awareness of the adolescent's reproductive health) website was used to educate students, and the next week team members conducted offline education and focus group discussion (FGD). The data collection used pretest and posttest questionnaires. The results showed an increase in the average knowledge of female and male adolescents before and after programs (47.79 ± 3.21; 81.14 ± 10.25) and (92.10 ± 4.93; 83.42 ± 7.09), respectively. In conclusion, health education with blended learning increases knowledge retention related to adolescent sexual reproduction.